Blockchain for Monitoring the Safe Supply Chain of Medicines: Reducing the Circulation of Illegal Drugs in Indonesia - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (Eastasouth Institute, 2025)
The pharmaceutical supply chain in Indonesia faces significant challenges, including counterfeit drug infiltration and insufficient traceability. This study explores the application of blockchain technology as a solution to monitor and secure the supply chain, reducing the circulation of illegal drugs. Using a qualitative approach, data were collected from five informants, including experts in blockchain technology, pharmaceutical supply chain management, and regulatory oversight. The findings reveal blockchain’s potential to enhance transparency, accountability, and regulatory compliance through features such as decentralized ledgers and smart contracts. However, challenges such as high implementation costs, technical barriers, and regulatory gaps hinder its adoption. The study concludes with recommendations, including capacity building, collaborative pilot programs, and the development of supportive policies, to facilitate blockchain integration in Indonesia’s pharmaceutical sector.